The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3122/jabfm.2017.01.160118
|View full text |Cite
|
Sign up to set email alerts
|

The Transition of Primary Care Group Practices to Next Generation Models: Satisfaction of Staff, Clinicians, and Patients

Abstract: Introduction:Restructuring primary care is essential to achieve the triple aim. This case study examines the human factors of extensive redesign on 2 midsized primary care clinics (clinics A and B) in the Midwest United States that are owned by a large health care system. The transition occurred when while the principles for patient-centered medical home were being rolled out nationally, and before the Affordable Care Act.Methods: After the transition, interviews and discussions were conducted with 5 stakehold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…49 Even 2 years after the implementation of CPS on interprofessional teams, PCPs continued to feel solely responsible for most tasks, 15 suggesting that an ethos of physician ownership over patients can be a barrier to achieving interprofessional collaboration. 50 Our findings also echo some Australian pharmacists' perceptions that PCPs deny their skills and dismiss their advice, which researchers interpreted as a demarcation of medical territory and an expression of "medical dominance." 51 On the other hand, PCPs have the opportunity to use their positional power to establish the CPS' collaborative role.…”
Section: Discussionsupporting
confidence: 76%
“…49 Even 2 years after the implementation of CPS on interprofessional teams, PCPs continued to feel solely responsible for most tasks, 15 suggesting that an ethos of physician ownership over patients can be a barrier to achieving interprofessional collaboration. 50 Our findings also echo some Australian pharmacists' perceptions that PCPs deny their skills and dismiss their advice, which researchers interpreted as a demarcation of medical territory and an expression of "medical dominance." 51 On the other hand, PCPs have the opportunity to use their positional power to establish the CPS' collaborative role.…”
Section: Discussionsupporting
confidence: 76%
“…13 The personal and professional responses by staff and clinicians to role redefinition can also affect practice transformation; sometimes leading to changes in personnel at a practice. 14 The more successful practices have strong physician facilitation, clearly defined roles and practice guidelines for all levels of staff and strong communication structures (such as team huddles, frequent team meetings) in place.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, an increasing number of elderly patients with coronary heart disease are selecting interventional therapy. Many studies have shown that PCI has the advantages of minimal trauma, fast recovery and fewer complications[8,9]. Every year, the rate of the number of patients undergoing PCI increases by 30%-40% in China[10].…”
Section: Introductionmentioning
confidence: 99%
“…Health management enables healthy and less healthy people to develop a good, orderly and healthy lifestyle by promoting health, motivating individual enthusiasm, reducing risk factors, and thus decreasing the incidence of disease. Studies have shown[8] that the period from 2–6 months after discharge is critical for patients to transition from the hospital to a community clinic or to care with family members for continuous treatment or health recovery. If we can strengthen health management during the transition period, it will have important clinical significance for the efficacy of treatment and the prognosis of the discharged patients.…”
Section: Introductionmentioning
confidence: 99%